The impact of a specific training programme on the selected parameters of swimming turns - Zuzuna Pupišová; Martin Pupiš; Jozef Sykora; David Brunn; Jana Giničová; Ratko Pavlović (Turkish Journal of Kinesiology, 2019)
The presented study focuses on the impact analysis of a specific training programme primarily focusing on plyometric exercises for the lower limb explosive power, and the selected parameters of swimming turns. The tested set consisted of performance swimmers (n = 20, men n = 12 and women n = 8) in the average age of 17.3 years, average height of 174.2cm, and average weight of 65.8kg. The tested set was divided into two smaller sets. The experimental set (n = 10) used the training process as an extra experimental factor and the supervision set (n = 10) carried out only the main contents of the training process. The specific training schedule was applied during the period of 8 weeks, three times a week for 20 minutes. The effectiveness of the experimental factor was tested through a selected set of tests, focusing primarily on the lower limb explosive power. Three of the tests were conducted on the dryland using the Myotest machine: T1 - Squat jump (SJ), T2 - Countermovement Jump (CMJ) and T3 - Plyometric jump (PJ). The tests conducted in the swimming pool were: T4 - max. length of floating up after the push off from the turning wall, and T5 - the length of push off after 25m of breaststrokes in the maximum speed with a push off from the wall of maximum floating up. The results pointed out a proportionally higher increase in the experimental set, in which the average percentile improvement of the jump height amounted to 17.7% in T1 (the changes in the supervision set were 0.7%); in T2 the jump height was increased by 22% (the changes in the supervision set were 0.6%); in T3 the time of contact increased by 18.5% (the supervision set showed a decrease by 1.2%), T4 by 14.9% (the changes in the supervision set were 4.1%) and in T5 by 22.7% (the changes in the supervision set were 11.0%). Kendall correlation coefficient (r), pointed out the average value of the correlation coefficient between the experimental factor and the individual tests as follows: T1: r = 0.39, p<0.05; T2: r = 0.41, p<0.05; T3: r = 0.43, p<0.05, T4: r = 0.38, p<0.05 a T5: r = 0.41, p<0.05. In conclusion, practice, improvement, and affectivity of the swimming turn can affect the swimmers' performance in races and improve it.